Вплив надлишкового вiд’ємного заряду на спектри поглинання та анiзотропiї збудження флюоресценцiї несиметричних полiметинових барвникiв - Borysyuk, V. I.; Yashchuk, V. M.; Naumenko, A. P.; Stanova, A. V.; Gerasova, V. G.; Gerasov, A. O.; Kovtun, Yu. P.; Shandura, M. P.; Kachkovsky, O. D. (Publishing house "Academperiodika", 2019)
The combined spectral and quantum-chemical investigations of the vinylog series of the asymmetric anionic polymethine dyes, derivatives of aminocoumarin, as well as the related symmetric dyes, are fulfilled. The charge injection to these types of dyes leads to the essential shifts of electronic levels. The calculations show the inverse character of the first two electron transitions in anionic polymethines and relative cationic polymethines. It is established that going to asymmetric dyes leads to a slight decrease of the spectral effect of the chromophore lengthening. The influence of the asymmetry manifests itself in a positive deviation in the absorption spectra and a negative deviation of the second electron transition manifested visually in the anisotropy of the fluorescence excitation spectra of asymmetric dyes. It is found that the lengthening of the chromophore is accompanied by an increase of the deviation of the first electron transition and, in contrast, by a decrease of the deviation of the second transition. The obtained results may be used in the design of molecular systems with prognosed current-voltage characteristics for nanoelectronics.